Legal Protection for Consumers and Business Actors in Selling and Buying Drugs Online - Hilda Muliana; Y. Budi Sarwo; Sabda Wahab; Ronny S utanto (SOEPRA, 2021)
Abstract: The process of buying and selling drugs online has risks and negative impacts that can harm the community. The process of buying and selling drugs already has laws and regulations that specifically regulate the sale and purchase of drugs. Business actors still easily buy and sell drugs online without limits and without regard to drug laws and regulations, which will be very risky for drug consumers. This study aims to determine and analyze how the regulation of legal protection and the implementation of legal protection for consumers and business actors in buying and selling drugs with an online system. The research method uses a sociological juridical approach with analytical descriptive specifications. Using secondary data and primary data obtained from library studies and field studies. The data were analyzed qualitatively and presented systematically and presented in the form of tables and narratives. The results of the study indicate that: (1) The regulation of legal protection for business actors and consumers in buying and selling drugs online is based on the Electronic Information and Transaction Law (UU ITE) and the Government Regulation on the Implementation of Electronic Transaction Systems (PP PSTE), the Consumer Protection Act. (UU PK) and Regulation of the Drug and Food Supervisory Agency Number 8 of 2020 concerning Control of Drugs and Food Circulated Online have provided legal protection to consumers and business actors, but the implementation has not been optimal, so there are still business actors who violate the provisions of the regulation. (2) The implementation of legal protection related to the process of buying and selling drugs online, both preventively and repressively, has not been maximally carried out, this can be seen from the increasing number of business actors selling illegal and counterfeit drugs online. The BBPOM of the City of Surabaya in collaboration with the Surabaya City Health Service and the Indonesian National Police (POLRI), needs to improve supervision, guidance, investigation, and investigation as well as monitoring and evaluating the implementation of online drug trading. Abstrak: Proses Jual beli obat secara online memiliki resiko dan dampak-dampak negatif yang dapat membahayakan masyarakat. Proses jual beli obat telah memiliki peraturan perundangan yang mengatur khusus tentang jual beli obat. Para pelaku usaha masih dengan mudah melakukan jual beli obat online tanpa batas dan tanpa memperdulikan peraturan perundangan obat-obatan, yang akan sangat beresiko kepada para konsumen obat. Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana pengaturan perlindungan hukum dan pelaksanaan perlindungan hukum terhadap konsumen dan pelaku usaha dalam transaksi jual beli obat dengan sistem online. Metode penelitian menggunakan pendekatan yuridis sosiologis dengan spesifikasi deskriptif analitis. Menggunakan data sekunder dan data primer yang diperoleh dari studi Pustaka dan studi lapanagan. Data dianalisis secara kualitatif dan disajikan secara sistematis dan disajikan dalam bentuk tabel dan narasi. Hasil penelitian menunjukkan bahwa : (1) Pengaturan perlindungan hukum terhadap pelaku usaha dan konsumen dalam jual beli obat online berdasarkan Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) dan Peraturan Pemerintah Penyelenggaraan Sistem Transaksi Elektronik (PP PSTE), Undang-Undang Perlindungan Konsumen (UU PK) dan Peraturan Badan Pengawas Obat Dan Makanan Nomor 8 Tahun 2020 Tentang Pengawasan Obat dan Makanan yang Diedarkan Secara Daring telah memberikan perlindungan hukum kepada konsumen maupun pelaku usaha namun pelaksanaannya belum optimal, sehingga masih ditemukan pelaku usaha yang melanggar ketentuan peraturan tersebut. (2) Pelaksanaan perlindungan hukum terkait proses jual beli obat secara online baik secara preventif dan represif belum makmimal dilakukan hal ini terlihat dari masih meningkatnya pelaku usaha yang menjual obat illegal dan palsu secara online. BBPOM Kota Surabaya dalam berkolaborasi dengan Dinas Kesehatan Kota Surabaya dan Kepolisian Republik Indonesia (POLRI), perlu meningkatkan pengawasan, pembinaan, penyelidikan, dan penyidikan serta monitoring dan evaluasi pelaksanaan jual beli obat secara online.